Development, construct validity and test-retest reliability of a field-based wheelchair mobility performance test for wheelchair basketball - de Witte, A. M. H.; Hoozemans, M. J. M.; Berger, M. A. M.; van der Slikke, R. M. A.; van der Woude, L. H. V.; Veeger, D. H. E. J. (Journal of Sports Sciences, 2018)
The aim of this study was to develop and describe a wheelchair mobility performance test in wheelchair basketball and to assess its construct validity and reliability. To mimic mobility performance of wheelchair basketball matches in a standardised manner, a test was designed based on observation of wheelchair basketball matches and expert judgement.